Who Executes Justice? Comparative Institutional Paths from Verdict to Prison - Widyawati, Anis; Adhari, Ade; Arifin, Ridwan (Universitas Negeri Gorontalo, 2026)
This article examines sentence-execution control in Indonesia, Thailand, and Tajikistan through the distinction between the Verdict Executor and the Criminal Executor as a basis for penitentiary law reform. It starts from the premise that the post-trial stage, particularly the enforcement of imprisonment, remains one of the least theorized yet most crucial parts of criminal procedure, with direct implications for legal certainty, institutional accountability, and prisoners’ human rights. Using normative legal research and a functional comparative approach, the study analyzes criminal sentence-execution systems, justice and imprisonment frameworks, relevant laws and regulations, institutional structures, and supervisory mechanisms in the three countries. The findings show important differences in the allocation of powers and functions between supervisory and executive bodies. Indonesia reflects an integrated model in which prosecutorial authority extends to the admission of convicts and the administration of sentences. By contrast, Thailand and Tajikistan adopt more differentiated institutional arrangements, with specialized and relatively independent bodies responsible for penitentiary supervision. The analysis concludes that judicial supervision of sentence enforcement and the execution of criminal punishment involve distinct doctrinal functions that should be institutionally separated. Such separation would reduce overlapping authority, minimize conflict, and improve systemic order and efficiency. In this context, the article argues that autonomous supervision of sentence execution should be recognized as a doctrinal category within criminal procedure law. It further proposes electronic supervision as a regulatory and procedural instrument to strengthen transparency, proportionality, and human rights compliance during the execution stage. Overall, the research demonstrates that without effective supervision of sentence execution, meaningful reform of the sentence-enforcement system and the rule of law remains unattainable.